Mathematical modeling for prediction of complicated acute appendicitis in children (Perioperaciina Medicina, 2018)
Endogenous intoxication, which accompanies the complicated course of acute appendicitis in children, is one of the serious conditions, which are the main cause of complications in the postoperative period. Diverse clinical observations done by clinicians suggest that despite the use of modern technologies in operating equipment, anesthetic support, the number of complications in the postoperative period has no tendency to decrease, and the main cause of lethal outcomes with appendicular peritonitis is lightning development of severe degree of endotoxicosis, which develops as a result of resorbing toxic substances formed of many components, including pathogenic microflora and destruction metabolism.Purpose. Creation of a mathematical model for prediction of complicated acute appendicitis in children using the functions of regression analysis of EXCEL spreadsheet by approximating experimental data.Materials and methods. In the work, there is information about 59 patients with acute appendicitis treated at the clinic of pediatric surgery at the National Pirogov Memorial Medical University. The data on patients were divided into two groups: patients with not complicated course of pathology – 24 patients, and patients with complicated course of acute appendicitis – 35 children. The control group served the data of 37 healthy children. In each of the three groups, the following parameters were studied: gender, age, bed day, duration of the disease, presence of symptoms of peritoneal irritation, the nature of exudate in the abdominal cavity, the number of red blood cells, hemoglobin, leukocytosis, quantitative characteristics of white blood formula, ESR, cellogenic endogenous intoxication: leukocyte index of intoxication and hematological index of intoxication. All the data were determined directly at the time of hospitalization of a patient to the hospital.Results. Discussion. Based on multiple correlation x = f (x1 , x2 ) a two-factor mathematical model of probability of the complicated course of acute appendicitis in children was created. According to the obtained results of the study of the system of three equations with three unknowns, it was established that if the indicator of the form of the disease is y = 2.67 and above, when, in numerical terms, the result falls into the zone of complicated flow of acute appendicitis and completely coincides with data analysis of the three groups of patients.Conclusions. The components that determine the uncomplicated course of acute appendicitis in children, according to the developed two-factor model, include LII and GPI, which exceed the values intoxication of certain intervals studied at the time of hospitalization. The analyzed indices were determined by the degree of severity of the pathological process, duration of disease, virulence of microflora and age of patients against the background of the formed endogenous intoxication syndrome.
Keywords: children; acute appendicitis; complicated flow; model